2020
DOI: 10.1111/1541-4329.12196
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an online piloted module targeted toward home‐based food operators in Iowa

Abstract: Understanding safe food practice is important for home‐based food operators to prevent foodborne illness. Earlier work has found that home‐based food operators lack food safety knowledge and may benefit from training that is specifically tailored to their needs. Unfortunately, home‐based food operators may be deterred from enrolling in traditional educational formats due to their busy schedules. The objective of this study was to pilot and evaluate the effectiveness of an online food safety education module fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Some recommendations for food workers that were identified are: (1) use extra resources, (2) use evaluations, and (3) use videos. Temen et al noted that using extra resources to help those struggling with difficult content was shown to help [ 59 ]. Costello et al recommended that evaluations are necessary to ensure that the content is understood [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some recommendations for food workers that were identified are: (1) use extra resources, (2) use evaluations, and (3) use videos. Temen et al noted that using extra resources to help those struggling with difficult content was shown to help [ 59 ]. Costello et al recommended that evaluations are necessary to ensure that the content is understood [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Costello et al recommended that evaluations are necessary to ensure that the content is understood [ 40 ]. Regarding findings for students, Temen et al found that including videos in training generated higher engagement and more improvement in their study [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation